75.9k views
4 votes
4(2x - 7) - 2x = -10​

User Suzanne
by
5.5k points

2 Answers

4 votes

Answer:

X = 3

Explanation:

distribute the 4 by everything, which gives you 8x-28-2x=-10 , then combine like terms (8x-2x) =6x, so you bring it down which gives you 6x - 28 = -10, then you add 28 to both sides, (-10 + 28) = 18, then bring that down, and then you have 6x = 18. then you just divide by 3

5 votes
you could use photomath for this but i got x=3, maybe search it up just in case
User Ramachandran
by
5.1k points